Pemberdayaan Istri Nelayan dalam Rangka Meningkatkan Pendapatan Keluarga melalui Pembuatan Garam di Desa Kuala Idi Cut Kabupaten Aceh Timur - Rosmaiti Rosmaiti; Fairus Fairus; Riezky Purnama Sari; Muhammad Salman; Amelia Amelia; Safrizal Safrizal; Ulya Nabilla; Muhammad Fuad; Kiagus Muhammad Zain Basriwijaya (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The fishermen's wife group is PKM Partners, who need empowerment. The limited knowledge and skills of partners in processing iodized salt and hygiene are problems that must be resolved. This community service aims to increase people's income, especially partners of fishermen's wives, by providing training and assistance in processing iodized and hygienic salt. The stages of this activity include 1) Socialization with partners regarding the processing of iodized and hygienic salt; 2) Salt processing training; 3) Financial bookkeeping training; 4) Monitoring and evaluation of PKM activities. The PKM method is the RRA (Rapid Rural Appreial) / PRA (Participatory Rural Appreial) method. This PKM produces iodized and hygienic salt products. Based on the questionnaire, it was found that 77% of partners are very understanding and skilled in processing iodized and hygienic salt, and 78% of partners strongly agree that this PKM activity can improve the quality of partners' salt.